Statement of Joseph W. Glauber Senior Research Fellow, International Food Policy Research Institute before the Senate Finance Committee - Glauber, Joseph W. (United States Senate Finance Committee, 2020)
Global agricultural trade has seen tremendous growth since creation of the WTO in 1995 and US agriculture has been a major beneficiary of the rules-based system that the United States and others helped create. The challenges to meet growing global food demand include population and income growth and supply uncertainties complicated by a changing climate, environmental pressures and water scarcity. All of those point to the increasing importance of trade and need for a more, not less, open trading system. A strong WTO is critical to helping meet future food needs.